The effect of low levels of sulphite on the swelling and solubility of starches - Paterson, Lorna A.; Mat Hashim, Dzulkifly; Hill, Sandra E.; Mitchell, John R. (WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim, 1994)
The effect of low levels of sulphite on the swelling volume and release of polysaccharide from a range of starches pasted at 95°C and 121°C has been investigated. In all cases the addition of 0.01% sulphite enhanced the release of polysaccharide on heating at 95°C and for potato, cassava and sago starches the measured volume showed a marked reduction. In the case of rice and wheat starches, sulphite only had a large effect on the swollen volume at pasting temperatures of 121°C, whereas, even at this temperature, maize was little affected. The addition of the polar antioxidant propyl gallate completely nullified the sulphite effect, with the exception of potato starch, suggesting that sulphite could act by promoting oxidative reductive de‐polymerisation of the polysaccharide. The effect of 0.01% sodium chloride was also investigated. It was found to have a similar effect to sulphite in the case of potato starch but did not influence the swelling volume or solubility of the other starches.